Best practices for teaching social studies : what award-winning classroom teachers do - Stone, Randi. 4 0 16; 5 (Thousand Oaks, CA : Corwin Press, 2008)
Contains seventeen articles in which teachers describe strategies they have used to help raise student achievement in social studies at the elementary through high school level.
Includes index.
Professional;Professional
Keywords: 2 -- 0; 6; Study and teaching -- Social sciences;Effective teaching -- United States;United States -- 20 -- Case studies.;Case studies; 20; 2